Implementasi Metode Role Playing untuk Meningkatkan Kreativitas Belajar Siswa dalam Pembelajaran IPS tentang Keanekaragaman Suku Bangsa Di Indonesia - Eva Herdiyana; Encep Supriatna (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Develop students' ability to understand the conditions that occur in society, especially the diversity of ethnic groups in Indonesia, which is very diverse. Here the researchers found a problem, namely the lack of social studies learning outcomes for students in class IV which showed that many students did not reach the KKM. because basically it only uses the lecture method, so that students are less active, do not realize knowledge in concrete life, are less able to develop their interests, students' critical thinking does not develop as well as thinking power which results in the value of student learning outcomes is not good. This research was carried out to students of class IV B Salira State Elementary School to 23 students. Two cycles have been carried out using classroom action research (CAR). The instruments used in the researchers were the student test sheet guidelines, student observation sheets, and teacher observation sheets. The results showed an increase in student learning outcomes. This increase is shown in the results of the pre-test and post-test scores on social studies learning about ethnic diversity in Indonesia, in the first cycle activities, the average score was 39.56 with a percentage value of 14.2% and at the post-test there was an average score. the average is 54.4 or the percentage is 25%. Then in cycle 2, students get an average pre-test score of 69.3 with a percentage value of 65.2%, and in cycle 2 the average score is 86.5 and the percentage value is 95.6%. With this, it can be seen that the value obtained by students in increasing creativity has increased, and students are also able to more easily study the material on ethnic diversity in Indonesia well, so that the material obtained in this study can be said to have been successful. This proves that the Role Playing method has a major impact on increasing students' creativity while studying.